Increasing Society Awareness about Climate Change Impacts and Adaptation and Mitigation Strategies in Rural Areas - Yunindyawati Yunindyawati; Yosi Arianti; Ridhah Taqwa; Rinto Rinto (Universitas Lambung Mangkurat, 2024)
This integrated scheme community service activity focuses on increasing society's awareness of climate change, its impacts, and mitigation and adaptation efforts that need to be carried out. This theme was chosen because climate change has become a global problem and needs to be addressed on the international, national, and local levels. Therefore, this community service activity is carried out to increase society's awareness about climate change. The activity will take place on August 6, 2023, at the Semambu Island Hall, North Indralaya district, Ogan Ilir Regency, South Sumatra. The target audience is comprised of residents of Semambu island, both men and women and a total of 30 people. The method of activity is empowerment, which provides material on the concept of climate change, the impact of climate change, mitigation efforts, and adaptation to climate change through counseling and mentoring methods. The results of this activity show that activities to increase society's awareness about climate change, its impacts, and mitigation and adaptation efforts that need to be carried out provide benefits in the form of increasing understanding and awareness of participants as target audiences. The understanding and awareness of activity participants increased by 26%. These results are obtained by comparing the pretest and posttest, carried out before and after the activity is carried out. Pretest and posttest are carried out by providing several questions in the form of questionnaires related to climate change material, the impact of climate change, mitigation, and adaptation to climate change. Thus, this activity is able and successful in contributing to increasing society's awareness about climate change in accordance with the objectives and benefits of the expected activities. The advice is that activities to increase society's awareness of climate change need to be continuously socialized to help the earth's safety. Related parties can follow up through programs related to saving the environment.